EFEKTIVITAS PELAKSANAAN ALSINTAN PADA KELOMPOK SASARAN - Wahyudi Narullova; Isralasmadi (UIR Press, 2023)
The main activity of this study is an effort to determine the effectiveness of the implementation of agricultural machinery for the target group as well as the community's response to the agricultural machinery assistance provided by the Ministry of Agriculture. In the form of interviews and filling out questionnaires. The research object consists of communities living in the same sub-district/village with farmers or farmer groups who receive benefits. The study location is the entire territory of Indonesia. This study aims to find out how effective the implementation of agricultural machinery is among the target group. The output of this study was in the form of identifying the benefits and problems that exist in the effectiveness of implementing agricultural machinery in the target group, as well as recommendations in the form of strategies that can be implemented in its development. From the results and discussions that have been carried out, it is concluded that the use of agricultural tools and machinery can increase the area and intensity of planting, speed up work, reduce costs, reduce losses, and increase production and productivity so that in the future we can create modern agriculture. Apart from that, the use of machinery can also provide economic or financial benefits.